Enhanced degradation of polycyclic aromatic hydrocarbons by indigenous microbes combined with chemical oxidation. (December 2018) - Liao, Xiaoyong; Wu, Zeying; Li, You; Luo, Junpeng; Su, Chunming
Abstract: In this study, the removal efficiency PAHs by chemical oxidation combined with microbe remediation was evaluated in two contaminated soils. The number of indigenous soil microbes decreased after the addition of chemical oxidants and then increased by nutrients addition. The total removal efficiencies of PAHs by chemical oxidation and nutrient addition followed the order: activated persulfate > potassium permanganate > modified Fenton reagent > Fenton reagent. There are 24.29–27.97%, 22.00–23.67%, 10.24–13.74% and 1.9–2.5% contributions separately due to nutrient treatment in Fenton, modified Fenton, activated persulfate and potassium permanganate treatment, which show significantly difference. The different chemical oxidants exhibited 78–90% removal efficiency for 5–6 rings PAHs, while 52–85% removal efficiency for 2–4 rings PAHs. With the addition of nutrients, the growth of indigenous microbes was enhanced significantly, and the contents of 2–4 rings PAHs in the soil were further decreased. Furthermore, the removal efficiencies of NAP and ANY were increased by more than 45%, while the removal efficiencies of ANE, FLE and PHE were about 30% at Fenton system. There was a complementary enhancing effect of microbial remediation for PAHs degradation after chemical oxidation. Graphical abstract: Highlights: A remediation strategy of chemical oxidation combined with microbial remediation were posed in this study. Indigenous microbes increased significantly after chemical oxidant peroxidation with addition of nutrients. The residual PAHs after chemical oxidant peroxidation could be further removed by indigenous microbes.